Microclimate along an elevational gradient controls foliar litter cellulose and lignin degradation in a subtropical forest - Chen, Bo; Yang, Yuting; Chen, Lyuyi; Jiang, Lan; Hong, Yu; Zhu, Jing; Liu, Jinfu; Xu, Daowei; Kuang, Kaijin; He, Zhongsheng (Frontiers in Forests and Global Change, 2023)
Cellulose and lignin are the principal constituents of plant litter, and their degradation plays an important role in the maintaining the soil carbon balance in terrestrial ecosystems. Yet, our knowledge of the responses of litter mass loss and cellulose and lignin degradation to litter quality, environmental factors, and taxonomic diversity indices along an elevational gradient in subtropical forests remains sparse. To gain insight into litter decomposition dynamics and its influencing factors, we investigated the cellulose and lignin degradation of foliar litter that from the two most dominant tree species along an elevational gradient (900–1,600 m) in a subtropical forest on Daiyun Mountain, China. Our results showed the following. (1) The degradation rate of cellulose was higher than that of lignin for litter collected at each elevation. The mass loss for foliar litter at different elevations was greater in the early period (0–180 days) than later period (180–270 days). (2) Litter quality, as well as environmental factors and taxonomic diversity indices, together influenced the foliar litter mass loss rate in addition to the rates of cellulose and lignin degradation. The key environmental factors included air and soil temperature, which had significant correlations with litter decomposition positively. The litter quality, namely is N (nitrogen) and P (phosphorus) contents, had significant positive correlations with degradation rates of cellulose and lignin in litter, and vice versa for lignin/N and C/N ratios. Some of the taxonomic diversity indices had positive correlations with litter decomposition, indicating that the input of highly diver litter material leads to a non-additive effect. (3) The litter decomposition was affected by the combination of litter quality, environmental factors, and taxonomic diversity indices. Of these, however, the environmental factors are the main factors that controlled the litter decomposition along elevational gradients in this subtropical forest. The results could provide a theoretical basis for understanding foliar litter nutrient release for the subtropical forest ecosystem of China.